A sequential ROMP strategy to donor–acceptor di-, tri- and tetra arylenevinylene block copolymers. Issue 46 (15th November 2021) - Komanduri, Venukrishnan; Janpatompong, Yurachat; Marcial-Hernandez, Raymundo; Tate, Daniel J.; Turner, Michael L.
Abstract : Sequential ROMP of electron rich and electron deficient paracyclophanediene monomers gives donor–acceptor di-, tri- and even tetrablock phenylenevinylene coploymers. Abstract : The synthesis of donor–acceptor di-, tri- and tetrablock copolymers via sequential ROMP of electron rich and electron deficient paracyclophanediene monomers using Grubbs ruthenium carbene initiator, G3, is discussed. Block copolymers were initially formed with a cis / trans alkene geometry and these can be readily photoisomerised to the all trans forms. The optical and electrochemical properties of these block copolymers were examined by theory and experiment, and it was found that the HOMO and LUMO energy levels are localised on the donor and acceptor blocks, respectively.